2019
DOI: 10.5223/pghn.2019.22.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synbiotic on the Treatment of Jaundice in Full Term Neonates: A Randomized Clinical Trial

Abstract: PurposeJaundice accounts for most hospital admissions in the neonatal period. Nowadays, in addition to phototherapy, other auxiliary methods are used to reduce jaundice and the length of hospitalization. This study aimed to investigate the effect of probiotics on the treatment of hyper-bilirubinemia in full-term neonates.MethodsIn this randomized clinical trial, 83 full-term neonates, who were admitted to the hospital to receive phototherapy in the first 6 months of 2015, were randomly divided into two groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This was similar to study conducted by Bisceglia M et al, and Ahmadipour et al, which showed that neonates receiving probiotics showed greater frequency of stools compared to that of those in placebo. 7,8 In a meta-analysis done by Chen et al, and study done by Mohammad et al, it was observed that probiotic supplementation increases the frequency of stool versus placebo. 9,10…”
Section: Resultsmentioning
confidence: 99%
“…This was similar to study conducted by Bisceglia M et al, and Ahmadipour et al, which showed that neonates receiving probiotics showed greater frequency of stools compared to that of those in placebo. 7,8 In a meta-analysis done by Chen et al, and study done by Mohammad et al, it was observed that probiotic supplementation increases the frequency of stool versus placebo. 9,10…”
Section: Resultsmentioning
confidence: 99%
“…19 A study conducted in Iran also showed that probiotics can reduce the serum total bilirubin levels when used as an adjunct to standard therapy. 20 A meta-analysis conducted by Chen Z et al provided evidence that the combination of routine treatment with probiotics including Bifidobacterium, S. boulardii, C. butyricum, probiotic oligosaccharides and B. subtilis had more efficacy in neonatal jaundice. Moreover, it was also helpful in reducing total bilirubin levels, time of jaundice fading, duration of phototherapy and hospitalization 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of probiotics and symbiotics is addressed by several authors, demonstrating the effectiveness of these microbiological preparations in reducing neonatal jaundice, avoiding the need for phototherapy or decreasing the time of exposure to it. According to Suganthi & Gokul Das (2016) and Ahmadipour et al (2019), these compounds are widely used in children to treat intestinal disorders, since their main effect on the human body is the stabilization of intestinal microflora; a better performing intestinal flora facilitates the passage of meconium, which is the main source of excretion of bilirubin 17,18 .…”
Section: (Citation Of the Review Articles) Corroborating What Is Already Recommended By The Americanmentioning
confidence: 99%